Synthesis and Antioxidant Activity of a New Series of 2,1-Benzothiazine 2,2-Dioxide Hydrazine Derivatives - Shafiq, Muhammad; Ullah Khan, Islam; Zia-ur-Rehman, Muhammad; Nadeem Asghar, Muhammad; M. Asiri, Abdullah; Nadeem Arshad, Muhammad (Asian Journal of Chemistry, 2012)
A convenient synthesis of a series of new N-benzylidene-N'-(1-ethyl-2,2-dioxo-2,3-dihydro- 1H-2l6-benzo[c][1,2]thiazin-4-ylidene)-hydrazines is reported. The starting compound methyl anthranilate was reacted with methane sulfonyl chloride, followed by N-ethylation and cyclization reactions. This cyclized 2,1-benzothiazine 2,2-dioxide molecule was then subjected for hydrazinolysis with hydrazine followed by condensation reactions with a number of aromatic aldehydes yielding the 2,1-benzothiazine 2,2-dioxide hydrazine. Structural elucidation was achieved by FT-IR, 1H and 13C NMR and single crystal X-ray diffraction analyses. Crystal structure data for 6a has been given with a brief structural discussion. The newly synthesized compounds were then screened for their antioxidant activity by ABTS radical cation decolourization assay and metal chelating activity.